Kajian Potensi Tumbuhan Sumber Pangan dan Pemanfaatannya di Gunung Tilu Kabupaten Kuningan - Yayan Hendrayana; Ilham Adhya; Nina Herlina; Ai Nurlaila; Fahrul Shohbarudin Syahban; Ali Jabar Rangga Wijaya; Wendra Wendra (Quagga : Jurnal Pendidikan dan Biologi, 2023)
The Mount Tilu forest area has a high biodiversity of both flora and fauna. In line with the ever-increasing population growth, the need for food sources has also increased. Food needs can be fulfilled because of the potential utilization of existing natural resources. Many plant species that have nutrients and other elements that are important for human food needs need to be studied further. The purpose of this research is to find out the potential of food plants and their utilization by the people around Mount Tilu. The research method used to determine the condition of the vegetation is using the Line Transect and Sample Plot Methods. Meanwhile, information on plant utilization was carried out by interviewing the community around the area. In the Tilu Mountain area, there were 4 types of plant sources of food sources of carbohydrates, 10 types of fruit-producing sources, 2 types of fatty oil producers, 4 types of dye sources, and 21 types of medicinal plant sources. Utilization of food source plants around Mount Tilu is consumed directly for one's own needs. Information regarding the existence of these food-source plants is very important as material for study for area managers and surrounding communities in the future